The Spirit of Freehand Brushwork in Chinese Oil Painting - Feng, Jiarui (Pacific International Journal, 2023)
Freehand Brushwork is a unique artistic language in Chinese painting and calligraphy, celebrated for its ability to express emotion and spirit in the process of artistic creation. This paper aims to explore the spiritual connotation and artistic aesthetics of Freehand Brushwork oil paintings, and to examine the use of traditional Chinese Freehand Brushwork techniques in the expression of Western painting. By reconstructing the language of oil painting expression with traditional Chinese techniques, the paper seeks to investigate the Freehand Brushwork spirit of Chinese oil painting, which is deeply rooted in the Chinese idea of the ’unity of heaven and man’ and ’respect for individuals’. The paper presents a critical analysis of the aesthetic and expressive features of Freehand Brushwork oil paintings, shedding light on the unique artistic characteristics of Chinese oil painting that distinguishes it from other painting styles. This paper contributes to the understanding and appreciation of Freehand Brushwork oil paintings and serves as a guide for artists seeking to master the Freehand Brushwork techniques in their artistic creations.